13, 000 years of fire history derived from soil charcoal in a British Columbia coastal temperate rain forest. Issue 7 (27th July 2016) - Hoffman, K. M.; Gavin, D. G.; Lertzman, K. P.; Smith, D. J.; Starzomski, B. M.
Abstract: Little is known regarding the fire history of high‐latitude coastal temperate rain forests in the Pacific Northwest (PNW) of North America. While reconstructing historical fire regimes typically requires dendrochronological records from fire‐scarred trees or stratigraphically preserved lake sediment data, this type of information is virtually non‐existent in this region. To describe the long‐term fire history of a site on the central coast of British Columbia, Canada, we radiocarbon‐dated 52 pieces of charcoal. Charcoal ages ranged from 12, 670 to 70 yr BP. Fires occurred regularly since 12, 670 yr BP, with the exception of a distinct fire‐free period at 7500–5500 yr BP. Time since fire (TSF) estimates from soil charcoal and fire‐scarred trees ranged from 12, 670 to 100 yr BP (median = 327 yr), and 70% of the sites examined had burned within the past 1000 yr. An increase in fire frequency in the late Holocene is consistent with the widely held hypothesis that anthropogenic fires were common across the PNW. We evaluate TSF distributions and discuss the difficulties in assigning actual fire dates from charcoal fragments with large inbuilt ages in a coastal temperate rain forest setting. We determine that a comprehensive approach using soil charcoal and fire scar analyses is necessary to reconstruct general trends in fire activity throughout the Holocene in this region.